Muskuloskeletal disorders among dental surgeons at selected private dental hospitals in Dhaka city - Jahana, KM Rownak; Israt, Silvana; Khan, Md Ali Afzal; Chowdhury, Tazdik G; Sharif, Ahmed Raihan; Quader, SM Abdul (Update Dental College Journal, 2015)
A descriptive cross-sectional study was conducted among 96 dental surgeons at selected private dental hospitals in Dhaka city (North). The objective of the study was to find out musculoskeletal disorders within dental surgeons at selected private dental hospitals in Dhaka city during the period between September to November 2012.Convenient sampling technique was used and information was gathered by face to face interview with a pre tested semi structured questionnaires. Among the respondents, 43.8% were of in the age group of 36 - 40 years age, 18.8% were in the age group of up to 35 years, and 13.5% were in the age group of 41 45 years and 19.8% in the age group of over 50 years. The 67.7% were male and 32.3% were female respondents. By professional educational level 36.4% were Bachelor in Dental surgery and 63.5% were post graduated. . Among the respondents 79.2% who had professional experience more than 10 years missing in practice due to MSD more than 29.2%who had professional experience more than 10 years or less. The reduction and prevention of MSDs among dental surgeons should include their education and awareness regarding the importance of work related risk factors. Update Dent. Coll. j: 2015; 5 (1): 10-14